Perancangan Antarmuka Situs Web Teknologi Modifikasi Cuaca untuk Pemantauan Indeks Kualitas Udara di Wilayah Perkotaan - Wijaya, Ade; Mutoha, Dimas Khabib (Journal of Computation Physics and Earth Science (JoCPES), 2022)
This heartfelt paper shares the thoughtful design and development of a website interface dedicated to supporting weather modification technologies through the vigilant monitoring of the Air Quality Index (AQI) in urban areas, especially in places burdened by high pollution levels, like Jabodetabek. The front-end website gently emphasizes visualizing vital parameters of air quality, such as particulate matter (PM2.5 and PM10), carbon dioxide (CO2), and ozone (O3) levels. By lovingly integrating this data into an accessible and user-friendly interface, the platform empowers users to monitor real-time air quality conditions with ease. The website aspires to provide essential stakeholders with crucial information for making compassionate decisions regarding weather modification efforts aimed at enhancing air quality for all. This study compassionately focuses on the front-end design, ensuring simplicity and clarity in presenting the complex environmental data that often overhelms us. Future work may tenderly include back-end integration for automated data updates and broadned functionalities, bringing even more support to this noble cause.